Numerical Simulation and Engineering Application of Temporary Stress Field in Coal Mine Roadway - Heng Zhang; Hongwei Ma; Chuanwei Wang; Qinghua Mao; Xusheng Xue (Applied Sciences)
The imbalance between excavation and mining is significant as it restricts the efficient development of coal resources. Slow tunneling speed is primarily due to the inability to concurrently conduct excavation and permanent support operations, and temporary support is considered a key solution to this problem. However, the mechanism by which temporary support affects the surrounding rock in unsupported are as remains unclear, hindering the assurance of stability in these areas and the determination of a reasonable unsupported span. To address this issue, this work proposed a stress distribution model as temporary support, elucidating the distribution law of support forces within the surrounding rock. By analyzing the stress differences between areas with and without temporary support, the stress field distribution characteristics of temporary support were determined. Subsequently, the evolution of stress and strain in the surrounding rock within unsupported areas was analyzed concerning changes in temporary support length, support force, and unsupported distance. The results indicated that, although temporary support does not directly act on unsupported areas, it still generates a supportive stress field within them. The maximum unsupported distance should not exceed 3 m, and there is a strong linear relationship between the optimal temporary support force and the unsupported span. Furthermore, the length of temporary support should not exceed 17 m from the tunnel face. The successful application of the shield tunneling robot system verifies that temporary support can ensure the stability of the surrounding rock in unsupported areas, confirming the validity of the temporary support stress distribution model. This research can be used to design and optimize cutting parameters and temporary support parameters, arrange equipment, and design and optimize tunnel excavation processes to achieve safe and efficient tunneling.